2017
DOI: 10.1007/s10461-017-1690-0
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Conspiracy Beliefs Related to Pre-exposure Prophylaxis (PrEP) and Interest in Using PrEP Among Black and White Men and Transgender Women Who Have Sex with Men

Abstract: The HIV/AIDS epidemic in the US continues to persist, in particular, among race, sexual orientation, and gender minority populations. Pre-exposure prophylaxis (PrEP), or using antiretroviral medications for HIV prevention, is an effective option, but uptake of PrEP has been slow. Sociocultural barriers to using PrEP have been largely underemphasized, yet have the potential to stall uptake and, therefore, warrant further understanding. In order to assess the relationships between potential barriers to PrEP (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(161 citation statements)
references
References 35 publications
7
150
2
Order By: Relevance
“…(3033) However, more recent studies using clinic-based and longitudinal cohort designs have found strong evidence of risk compensation among MSM in the U.S.(34–36) In terms of PrEP stigmatizing beliefs, a recent study of Black and White MSM and transwomen found that 70% thought PrEP would cause risky sex, and 23% believed that only promiscuous people use PrEP. (37) Other studies of MSM have found similarly prevalent negative PrEP beliefs across all demographics, although PrEP stigma among Black MSM is more connected to medical mistrust and other forms of stigma (HIV, LGBT, etc.) than White MSM.…”
Section: Introductionmentioning
confidence: 93%
“…(3033) However, more recent studies using clinic-based and longitudinal cohort designs have found strong evidence of risk compensation among MSM in the U.S.(34–36) In terms of PrEP stigmatizing beliefs, a recent study of Black and White MSM and transwomen found that 70% thought PrEP would cause risky sex, and 23% believed that only promiscuous people use PrEP. (37) Other studies of MSM have found similarly prevalent negative PrEP beliefs across all demographics, although PrEP stigma among Black MSM is more connected to medical mistrust and other forms of stigma (HIV, LGBT, etc.) than White MSM.…”
Section: Introductionmentioning
confidence: 93%
“…PrEP has been stigmatized because antiretrovirals with the same appearance are used for HIV treatment, and PrEP users may be mistakenly labeled as “HIV positive” . PrEP may also be seen as promoting sexual promiscuity, leading to stigma related to norms around sexuality in adolescent girls and young women (AGYW) .…”
Section: Introductionmentioning
confidence: 99%
“…PrEP demonstration programmes have found that women can initially adhere to PrEP , but adherence wanes over time with stigma remaining a barrier to sustained PrEP use during periods of HIV risk . Stigma can be particularly high in contexts where community awareness about PrEP is low, cultural norms dictate that unmarried women should not be sexually active or should practice monogamy, and PrEP was initially prioritized for “high‐risk” key populations, including female sex workers (FSWs) . Quantitative analyses among men who have sex with men (MSM) in the United States and Africa and heterosexual women in the United States have found that stigma significantly reduces PrEP interest, uptake and adherence .…”
Section: Introductionmentioning
confidence: 99%
“…The barriers that respondents acknowledged mirrored those identified in studies examining PrEP‐related barriers for marginalised racial groups in the United States. Black GBM had difficulty accessing PrEP due to health illiteracy, 26 stigma, 27 mistrust of the medical profession, 28 and a lack of culturally appropriate healthcare services 29 . This supports the contention that people who experience different forms of intersecting marginalisation may struggle to access preventative healthcare interventions due to a confluence of complex socioeconomic factors, and supports the need for consideration of intersectionality issues for Aboriginal GBM 30 …”
Section: Discussionmentioning
confidence: 99%